Grazing lambs on pastures regrown after wildfires did not significantly alter metal content in meat and wool - Sarah Depenbrock; Jennie Lane; Makda Asrat; Robert Poppenga; Sabine Hargrave; Bret McNabb; Valerie Eviner; Munashe Chigerwe (California Agriculture, 2023)
Wildfires can drastically change rangeland by depositing ash contaminated with metals that are not part of normal diets. This can pose health threats to humans and animals. This risk, along with alterations of essential minerals in livestock grazing on regrowth on burnt lands, is not well known. To better understand this, our study investigated metal concentrations in water, soil, plant forage, and meat and wool of sheep grazing on the regrowth of burned lands. We compared metal concentrations in sheep grazed on regrowth to stored meat samples from grazing sheep a year prior to the wildfire. Lead, mercury, arsenic, molybdenum, cadmium, beryllium, cobalt and nickel were not detected above reporting limits in meat, wool or water samples. Contamination from chromium and thallium was detected in three of 26 meat samples from sheep grazed on regrowth. These metals were not detected in 22 stored meat samples from sheep the year before. Copper concentrations found in the meat of animals grazing regrowth was lower than in animals grazing unburned pastures; it is important to monitor copper concentrations in grazing animals to avoid diseases associated with copper deficiency.